EFEITO DA ADIÇÃO DE POTÃSSIO SOBRE O PH DE ALGUNS SOLOS DO ESTADO DE SÃO PAULO - Mello, Francisco de A. F. de; Cardoso, Antonio; Athayde, Manoel L. F.; Demattê, Maria E. P.; Pitelli, Robinson A.; Arzolla, Sylvio (REVISTA DE AGRICULTURA, 2020)
EFEITO DA ADIÇÃO DE POTÃSSIO SOBRE O PH DE ALGUNS SOLOS DO ESTADO DE SÃO PAULO